L’intervention auprès de jeunes mères et de leur enfant : perspective de la théorie de l’attachement - Tarabulsy, George; Robitaille, Julie; Lacharité, Carl; Deslandes, Julie; Coderre, Rémi (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1998)
The children of adolescent mothers are among those presenting the highest level of psychosocial risk, compromising their socio-emotional development on a number of levels. Several intervention strategies have been designed to address some of the problems that characterize these mother-infant dyads. While these strategies have proven to be beneficial to young mothers, relatively little impact has been found on the level of infant and child development. The purpose of this article is to address the issue of intervention aimed at adolescent mothers and their infant, and underline that the relational dimension, while absent from most intervention programs, is necessary to our understanding of the problems presented by these dyads. An intervention program, currently undergoing evaluation, is described having as a main objective the improvement of the early mother-infant relationship. Attachment theory is presented as an organizing construct. Characteristics of the intervention, as well as the evaluation strategy, are described.